Intraosseous lines in preterm and full term neonates. Issue 1 (1st January 1999) - Ellemunter, Helmut; Simma, Burkhart; Trawöger, Rudolf; Maurer, Heiner
Abstract : AIM: To evaluate the use of intraosseous lines for rapid vascular access in primary resuscitation of preterm and full term neonates. METHODS: Thirty intraosseous lines were placed in 27 newborns, in whom conventional venous access had failed. RESULTS: All the neonates survived the resuscitation procedure, with no long term side effects. CONCLUSION: Intraosseous infusion is quick, safe, and effective in compromised neonates.